2023
DOI: 10.21203/rs.3.rs-2563665/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemic intelligence activities among national public and animal health agencies: a European cross-sectional study

Abstract: Epidemic Intelligence (EI) encompasses all activities related to early identification, verification, analysis, assessment, and investigation of health threats. It integrates an indicator-based (IBS) component using systematically collected surveillance data, and an event-based component (EBS), using non-official, non-verified, non-structured data from multiple sources. We described current EI practices in Europe by conducting a survey of national Public Health (PH) and Animal Health (AH) agencies. We included … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Our study showed that the infrastructures of EI systems and the strategies for early warning and surveillance of EIDs vary across European countries and between national and regional levels, despite recommendations of supranational agencies (7). The organization of surveillance and collaborations were different according to the disease as stated also in a recent cross-sectional study (12). Despite these differences, all countries in our study bene ted from the creation of a Health Information System (HIS) with different components that are common for many other European countries (6).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our study showed that the infrastructures of EI systems and the strategies for early warning and surveillance of EIDs vary across European countries and between national and regional levels, despite recommendations of supranational agencies (7). The organization of surveillance and collaborations were different according to the disease as stated also in a recent cross-sectional study (12). Despite these differences, all countries in our study bene ted from the creation of a Health Information System (HIS) with different components that are common for many other European countries (6).…”
Section: Discussionmentioning
confidence: 78%
“…They combined mandatory communicable disease noti cations, sentinel surveillance network with local stakeholders, event-based surveillance, and syndromic surveillance during mass gatherings. The most interoperable and timely databases at national level were those from laboratories, whose importance for early warning have been recently con rmed, by a quantitative study, for many models (12), and the shared platforms were useful for intersectoral collaborations although they cannot be extended to all models. Inside EI, the practices and logics of users showed activities that span from detection to reporting, rather than siloed activities for epidemic preparedness and response as previously described by Barboza (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, for the societal context, events or restrictions can in uence the content and latest trends. These observations con rm the importance of semi-automatisation and the requirement of human supervision during machine learning and text extraction, especially during the pandemic when European disease surveillance agencies lack human resources (24). Unfortunately, Twitter data rst used as experimental ground were no longer used in PADI-Web but remained a valuable source of data for ProMED.…”
Section: Discussionmentioning
confidence: 98%